A study on curved surface laser ablation using beam profile approach. (2017) - Garg, Vivek; Marla, Deepak; Joshi, Suhas S.
Laser ablation process was used to generate micro-scale curved surfaces that find applications such as micro-lens and hydrophobic surfaces. Curved surface laser ablation to produce micro-scale features generally involves altering the spatial beam profiles using masks with varying spatial opacity. The surface profile obtained mainly depends on the altered laser beam profile. This work aimed at understanding the influence of laser beam profile on the generated surface in curved surface laser ablation. The study was based on a 2D finite element model of laser ablation that considered target heating, heat transfer and vaporisation on a poly methyl methacrylate (PMMA) target. Using this model, surface profile was predicted for various profiles of laser intensity and a qualitative analysis of curved surface profiles was carried out. The quantitative comparison of the ablation depths for uniform beam was used to validate the numerical model. The results of ablation depth were found to be in good agreement with that of the experiments.